Social cultural influences on current and future coastal governance - Hofmeester, Carolyn; Bishop, Brian; Stocker, Laura; Syme, Geoffrey (World Future Society, 2012)
Australians have strong attachments to the coast. The impact of climate change brings to the fore deep-seated socio-cultural values, which add to the already complex and uncertain biophysical changes that challenge our preparations for future climate change. Our research aims to examine the role of worldviews and deep seated values in decision-making in response to climate change. The objective is to show how a multi-layered discourse analysis using causal layered analysis (CLA) can provide a powerful means of revealing the underlying social and cultural influences on decision-making and provide more insight into potential pathways for more effective responses to complex phenomena such as climate change. A case study of coastal governance in the south west of Western Australia, which is highly vulnerable to sea-level rise, provides the context of the research.We have found that CLA as a critical research tool has proven to be a useful method in uncovering the dominance of the administrative rationalist worldview on coastal governance. In our view, future coastal governance would benefit from a shift towards greater participatory governance and the incorporation of more reflexive practice so that the deeper emotional and relational aspects of decision-making balance out the dominant problem-solving discourse.